USER SATISFACTION OF MEDICAL EDUCATIONAL SERVICES - STOICA, Ivona (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
In a dynamic environment and a strongly focused on the needs and demand’s consumer, any successful business is based on a complex analysis achieved by using marketing research. The paper’s  core represents a marketing research whose aim is to analyze user satisfaction of medical educational service. The quantitative marketing research was based on a statistical survey method, using a questionnaire as a collecting tool posted on a web platform for better access, visibility and transparency in completing the form. After the development of a professional training session on medical education, it has been developed a study regarding the participants' satisfaction in terms of quality, utility, informational content and presentations efficiency. We analyzed variables such as respondents' appreciation regarding the quality of materials received, the value information, the event capitalization by establishing relationships with tutors communication, quality service and appreciations regarding the location of medical training session, default services (accommodation, ambiental atmosphere), event quality the ground objective variables in medical education services satisfaction case study. This paper presents a multivariate analysis, based on correlations between variables measuring user satisfaction of services on medical education services which are the ground’s conclusions and strategies to improve medical education services.